PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE - Perkasa, Ridho Deza; Syentia, Likanopa; Yentisna, Yentisna (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2025)
This research aims to empirically examines the influences of corporate governance mechanism on tax avoidance. The research’s population of this study are manufacturing Companies listed in the Indonesia Stock Exchange (BEI) in 2014-2017, which is 97 companies. This research samples were to 54 companies or 216 observation data selected by purposive sampling method. The data used is secondary data obtained from the Indonesia Stock Exchange (IDX) and it was analyzed by descriptive statistics, classic assumption test, goodness of fit model. The results of the research shows that independent board of commissioners and audit quality positively affect Tax Avoidance. whereas the institutional ownership and board of directors does not affect Tax Avoidance.